The position of women in the Muslim family between cultural construction and textual foundation: a critical analysis within the Wasatiyyah framework - Haneef, Sayed Sikandar Shah; Abdullah, Ismail (Research Management Centre, International Islamic University Malaysia, 2016)
The question of the position of women in the family in the contemporary Islamic literature is one the much contested issues between the vanguards of orthodoxy and Muslim feminist advocates. To the conservative `ulama, predominantly, in spite of a great deal of custom based laws conferring somewhat reduced rights to the women are part of immutable Shari`ah law. The Muslim feminist, on the other hand, argue that not only custom but also cultural assumptions and norms of the patriarchy as embedded in both pre-Islamic and medieval patriarchal cultures are responsible for suppressing the egalitarian principles of the Qur`an and normative Sunnah through their extrapolation by the male jurists and exegetes. To deal with this dichotomy, emotion runs high on both sides and the approaches, by and large, have been rhetorical. The middle of the road approach (wasatiyyah) anchored in sound Islamic methodology of renewal no doubt has voiced itself haphazardly in the form of obiter dictums here and there. This study argues and engages with both the mainstream conservative views (muhafazawiyyah) and that of feminist positions (`Unthawiyyah),from wasatiyyah perspective.